2022
DOI: 10.1021/acscatal.2c00092
|View full text |Cite
|
Sign up to set email alerts
|

Operando XAS Study of Pt-Doped CeO2 for the Nonoxidative Conversion of Methane

Abstract: The methane to olefins, aromatics, and hydrogen (MTOAH) process via Pt/CeO 2 catalysts poses an attractive route to improve yield and stability for the direct catalytic conversion of methane. In this study, two sets of samples, one composed of PtO x single sites on ceria and the other with additional Pt agglomerates, were prepared. Both sets of samples showed enhanced catalytic activity for the direct conversion of methane exceeding the performance of pure ceria. Pulsed reaction studies unraveled three reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
(133 reference statements)
2
21
0
Order By: Relevance
“…517,518 The formation of alloy nanoparticles induced by SMSI has also been observed in Pt/CeO 2 catalyst, in which the Pt−Ce bonding is formed after exposure to CH 4 at 975 °C. 519 The formation of Pt−Ce bonding could be understood as the reduction of CeO 2 support, and it requires higher temperature than the formation of Pt−Ti bonding in Pt/TiO 2 catalyst, which should be related to the reducibility of the oxide support. It is shown that, SMSI can occur after reduction by H 2 at 975 °C, while the reduction at 550 °C cannot trigger the SMSI in Pt/ CeO 2 .…”
Section: Bimetallic Nanoparticles Derived From Metal−support Interactionmentioning
confidence: 99%
“…517,518 The formation of alloy nanoparticles induced by SMSI has also been observed in Pt/CeO 2 catalyst, in which the Pt−Ce bonding is formed after exposure to CH 4 at 975 °C. 519 The formation of Pt−Ce bonding could be understood as the reduction of CeO 2 support, and it requires higher temperature than the formation of Pt−Ti bonding in Pt/TiO 2 catalyst, which should be related to the reducibility of the oxide support. It is shown that, SMSI can occur after reduction by H 2 at 975 °C, while the reduction at 550 °C cannot trigger the SMSI in Pt/ CeO 2 .…”
Section: Bimetallic Nanoparticles Derived From Metal−support Interactionmentioning
confidence: 99%
“…This is because of a charge transfer from La to Pd species . Moreover, the higher reduction temperature for the 1%Pd-Ce/Al 2 O 3 is probably attributed to the strong Pd-Ce interaction. …”
Section: Resultsmentioning
confidence: 98%
“…For example, Eggart et al prepared two groups of 0.5–1% Pt-loaded CeO 2 catalysts with unequal Pt dispersion and oxidation states. 72 Operational XAS combined with theoretical simulations demonstrated an increase in Pt–Ce interaction when reacting with CH 4 at 975 °C. Analysis of the extended EXAFS spectra demonstrated the modification and packaging of Pt the particles by the CeO 2 /Ce 2 O 3 carriers or partial Ce–Pt alloy formation due to SMSIs.…”
Section: Characterizationmentioning
confidence: 95%